2003
DOI: 10.1161/01.hyp.0000102863.23854.0b
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Increases NHE-1 Expression and Induces NHE-1-Dependent Hypertrophy in Neonatal Rat Ventricular Myocytes

Abstract: Abstract-We determined the effect of 24-hour aldosterone (100 nmol/L) treatment on hypertrophic responses in rat neonatal ventricular myocytes and the possible role of Na ϩ -H ϩ exchange isoform 1 (NHE-1). Aldosterone significantly increased cell size by 61% and expression of atrial natriuretic peptide by 2-fold. NHE-1 mRNA expression and protein abundance were significantly increased, and intracellular Na ϩ levels were elevated. Both hypertrophy and elevated Na ϩ levels were prevented by the NHE-1-specific in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 34 publications
8
75
0
6
Order By: Relevance
“…6). In contrast, p38 phosphorylation has been shown to be reduced by short-term aldosterone stimulation in NRCMs (Karmazyn et al 2003), indicating the possibility that aldosterone preconditioning attenuates the maladaptive p38 activation induced by IRI. The 27-kDa small heat-shock protein (HSP27) is a major downstream regulator of p38MAPK signaling cascades, whose phosphorylation has been shown to protect against IRI (Sanada et al 2001, Marais et al 2005.…”
Section: Discussionmentioning
confidence: 95%
“…6). In contrast, p38 phosphorylation has been shown to be reduced by short-term aldosterone stimulation in NRCMs (Karmazyn et al 2003), indicating the possibility that aldosterone preconditioning attenuates the maladaptive p38 activation induced by IRI. The 27-kDa small heat-shock protein (HSP27) is a major downstream regulator of p38MAPK signaling cascades, whose phosphorylation has been shown to protect against IRI (Sanada et al 2001, Marais et al 2005.…”
Section: Discussionmentioning
confidence: 95%
“…9,11,18,29 Besides its well-known genomic actions, aldosterone induces rapid cellular responses by activating signaling pathways independently of genomic effects. [17][18][19][20][21][22][23][24][25][26][27][28][29] The protein tyrosine kinase c-Src is abundant in the vasculature and appears to be an important signaling molecule in VSMCs. c-Src induces activation of MAPKs (p38MAPK, c-Jun NH 2 -terminal kinase, and ERK1/2), which are associated with cell growth, apoptosis, and collagen deposition.…”
Section: Aldosterone Effects On [ 3 H]proline Incorporationmentioning
confidence: 99%
“…Aldosterone induces rapid cellular responses by modulating intracellular calcium (Ca 2ϩ ) and cAMP levels, Na ϩ /H ϩ exchanger activity, and phosphorylation of signaling molecules, including protein kinase C, epidermal growth factor receptor, and mitogen-activated protein kinases (MAPKs), including c-Jun NH 2 -terminal kinase, and extracellular signal-regulated kinases (ERKs) 1/2. [17][18][19][20][21][22][23][24][25][26][27][28] We recently demonstrated that aldosterone rapidly increases activation of p38 MAPK and NAD(P)H oxidase through c-Src-dependent pathways in vascular smooth muscle cells (VSMCs). In addition, the profibrotic action of aldosterone was dependent on c-Src-regulated p38 MAPK.…”
mentioning
confidence: 99%
“…These results reveal a model to understanding the molecular regulation of miRNAs in cardiac hypertrophy. (17)(18)(19)(20). We attempted to understand whether miRNAs participate in conveying their hypertrophic signals.…”
mentioning
confidence: 99%